The Current State of Treatment for Cannabis Use Disorder - Dmochowska, Joanna; Mikos, Eryk; Kanon, Karol; Moqbil, Sara; Wasyluk, Martyna (Journal of Education, Health and Sport, 2022)
Cannabis remains the most commonly used illicit psychoactive drug and contains substances that affect the brain and body. A range of acute and chronic health problems associated with cannabis use has been identified. Cannabis use disorder is defined as the continued use of cannabis despite clinically significant impairment. It is estimated that 1 in 10 people who use marijuana will become addicted. CUD is a problematic pattern of cannabis use that causes clinically significant impairment. There is not an available medication to successfully treat CUD, but psychotherapeutic models hold promise. Cognitive behavioural therapy, motivational enhancement therapy and contingency management can substantially reduce cannabis use and cannabis-related problems. The legalization of non-medical cannabis use in some high-income countries may increase the prevalence of CUD. Since this approach has not yet been validated for CUD, the improvement of psychosocial treatments with pharmacological therapies should be further explored in future clinical research.